3-D study of vessels in peripheral placental villi - Jirkovská, Marie (Image analysis and stereology, 2007)
The microvascular bed of the human term placenta is located in the mature intermediate and terminal villi. Despite repeated studies, a commonly acceptedmodel of its spatial organization is not yet available. In the presentstudy, the 3-D arrangement of vessels in mature intermediate and terminal placental villi was examined using the combination of confocal microscopy and image processing. Fixed and paraffin embedded placental sampleswere cut into 120 ?m thick sections. Serial optical sections were captured by a confocal microscope and used as an initial data for 3-D reconstruction. The reconstructed segments of the villous tree show parallel vessels of mature intermediate villi giving rise to the capillaries of terminal villi. The signs of longitudinal and sprouting capillary growth as well as growth of new villi were observed. The presented method allowed us to visualize large parts of peripheral placental villi, which is useful for elucidating the arrangement of their vascular bed.
Keywords: Chorionic Villi; Horionske resice; Kapilare; Ultrastructure; Image Processing, Computer-Assisted; Slika, obdelava z računalnikom; Capillaries; Mikroskopija konfokalna; mikroskopiranje; Microscopy, Confocal; placenta